Gambaran Anatomi dan Histologi Testis Ayam Hutan Hijau (Gallus varius) Asal Pulau Alor - Lando, Lidya Olu; Maha, Inggrid T; Amalo, Filphin A; Foeh, Nancy D.F.K (Jurnal Veteriner Nusantara, 2024)
Green junglefowl (Gallus varius) is one of the endemic fowl in Indonesia. Testes are reproductive organs that play an important role in spermatogenesis. This study aims to describe the anatomical morphology and histology of the green junglefowl testes. The sample is 3 pairs of testes collected from 3 adult male green junglefowl from Alor Island with body weight range about 600 grams to 800 grams and age range about 1 to 2 years. The sample were observed macroscopically including the location, shape, color, consistency, weight, length and width. Furthermore, the sample were fixed with 10% formalin solution and continued with the process of making preparations and staining with hematoxylin-eosin (HE). The results showed that the testes of the green junglefowl were located in the abdominal cavity which was seen by the mesorchium. The testes are adjacent to several organs such as kidney, liver, spleen and proventriculus. The testes are asymmetrical, that is the left testicle is longer than the right testicle, while the width of the testicle is between 1.1 mm to 3.4 mm. The testicular weight is <1 gram. The testes are light yellow in color, have a smooth surface and are soft in consistency. Histologically, the testes of jungle fowl are composed of seminiferous tubules and interstitial tissue, and surrounded by a testicular capsule consisting of layers of tunica serous, tunica albuginea and tunica vasculosa. Sertoli cells and spermatogenic cells consisting of spermatogonia, primary spermatocytes, secondary spermatocytes and spermatids are scattered in the seminiferous tubules. The interstitial testes contain several components such as connective tissue, Leydig cells and blood vessels.